2018
DOI: 10.3126/nmj.v1i2.21579
|View full text |Cite
|
Sign up to set email alerts
|

Study on Correlation between Serum Prostate Specific Antigen and Various Prostatic Pathology

Abstract: Introduction: Prostatic enlargement that may due to any cause may give rise to bladder outlet obstruction. Prostatic specific antigen is the enzyme that is responsible for liquefaction of semen within a few minutes after it has clotted. Prostatic specific antigen is a widely used tumor marker for prostatic cancer. Prostatic specific antigen levels in the blood go up if the barrier between the lining epithelium and the blood stream is damaged. This study was done to determine the correlation between serum Prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Its concentration is also increased in BPH (benign prostatic hyperplasia), PIN (prostatic intra-epithelial neoplasia) and prostatitis. 3 Concentration above 4 ng/ml is considered abnormal. Prostate cancer prevention trial (PCPT) study, which included biopsy regardless of PSA level, demonstrated that there is no level of PSA below which prostate cancer risk falls to zero.…”
Section: Introductionmentioning
confidence: 99%
“…Its concentration is also increased in BPH (benign prostatic hyperplasia), PIN (prostatic intra-epithelial neoplasia) and prostatitis. 3 Concentration above 4 ng/ml is considered abnormal. Prostate cancer prevention trial (PCPT) study, which included biopsy regardless of PSA level, demonstrated that there is no level of PSA below which prostate cancer risk falls to zero.…”
Section: Introductionmentioning
confidence: 99%